The Response of white yam (dioscorea rotundata poir) tuber portions to positive selection for quality seed yam production (2017)
The production of yams is constrained by high cost and unavailability of clean planting materials, pests and diseases. Vegetative propagation has also caused a build of up diseases, reported to cause up to 80% yield reduction due to scarcity of quality declared seeds. Planting of disease-free material has been found to be effective in reducing disease problems in plants. This study was conducted to produce clean seed yam by reducing yam diseases through positive selection method. In this method, apparently healthy yam plants were identified, tagged (positive selection), assessed for yam mosaic virus incidence and severity using the scale 0 or 1 and 1-5 respectively. The harvested clean tubers from tagged plants were planted the following season so as to determine the rate of response of each genotype and tuber portion to positive selection. At the end of two cycles of positive selection, analysis of variance for percentage number of positive yam plants, YMV incidence, YMV severity and tuber yield shows significant difference (p ≤ 0.05) between positive selection and no selection for both field and screen house plants. It was observed that positively selected plants performed significantly (p ≤ 0.05) better than no selection plants. For field experiment, Number of positively selected plants was highest in positive TDr89/02665 with mean value of 75.00% while no selection Ogoja had the least number of positive plants (17.8%). A yield increase of 1.80 t/ha was recorded due to the application of positive selection method in two cycles. For screen house experiment, result followed a similar trend; however, with a reduction in YMV incidence and severity. It is worthy to note that tail portions of yam were lest infected with YMV, hence more healthy plants were selected from the tail portion.